2006
DOI: 10.1080/10611860600720814
|View full text |Cite
|
Sign up to set email alerts
|

LimitedP-glycoprotein mediated efflux for anti-epileptic drugs

Abstract: A variety of anti-epileptic drugs (AEDs) were tested for their ability to be transported by P-glycoprotein (P-gp) through Caco-2 monolayers using bi-directional (apical (Ap) to basolateral (Bas), and Bas to Ap) studies. Transport rates were equivalent in both directions for vigabatrin, gabapentin, phenobarbitone, lamotrigine and carbamazepine, being 0.7 x 10- 6, 0.1 x 10- 6, 34 x 10- 6, 36 x 10- 6 and 55 x 10- 6 cm/s, respectively. Phenytoin displayed a 20% increase in Ap to Bas transport, while topiramate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 46 publications
1
36
1
Order By: Relevance
“…Drug transport was studied with an in vitro gastrointestinal model by using a monolayer of a CLEFF9 subclone of human Caco-2 cells with high P-gp-mediated efflux (4) and previously reported experimental protocols (3)(4)(5). Briefly, cells were seeded onto 0.6-cm 2 polycarbonate filters in 24-well plates and grown in high-glucose Dulbecco's modified Eagle's medium for 3 weeks.…”
mentioning
confidence: 99%
“…Drug transport was studied with an in vitro gastrointestinal model by using a monolayer of a CLEFF9 subclone of human Caco-2 cells with high P-gp-mediated efflux (4) and previously reported experimental protocols (3)(4)(5). Briefly, cells were seeded onto 0.6-cm 2 polycarbonate filters in 24-well plates and grown in high-glucose Dulbecco's modified Eagle's medium for 3 weeks.…”
mentioning
confidence: 99%
“…The findings by Tishler et al were confirmed by other groups (Dombrowski et al, 2001;Lazarowski et al, 1999;Sisodiya et al, 2002) and it was suggested that this phenomenon could prevent AEDs from entering the brain and cause AED resistance. However, studies in cell lines of non-brain endothelial origin showed that some AEDs such as vigabatrin, gabapentin, phenobarbitone, lamotrigine, carbamazepine, and phenytoin are not, or are only weak, P-gp substrates, questioning whether P-gp could be the primary reason for AED resistance (Crowe & Teoh, 2006;Maines et al, 2005;Owen et al, 2001;Weiss et al, 2003). In contrast, Cucullo et al, compared phenytoin permeation in brain capillary endothelial cells from drug-resistant epileptic human brain tissue with that of commercially available human brain microvascular endothelial cells (Cucullo et al, 2007).…”
Section: Transporters In Epilepsymentioning
confidence: 99%
“…The inhibitors included the P-gp inhibitors PSC-833 (4 μM) or GF120918 (4 μM), as used previously (21). The general MRP inhibitor probenecid (at 500 μM) was also used.…”
Section: P-gp and Other Transport Inhibitionmentioning
confidence: 99%
“…Caco-2 sub clone cells, highly expressing P-gp, were seeded onto Millicell polycarbonate 0.6 cm 2 filter inserts in 24-well plates at 65,000 cells/cm 2 , as described previously (21). Cells were grown in 'growth medium' [high glucose DMEM with 25 mM HEPES (pH 7.4), 2 mM glutamine, 1 mM non-essential amino acids, 100 U/mL penicillin-streptomycin, and 10% FCS] in a 37°C incubator with 5% CO 2 .…”
Section: Cell Culturementioning
confidence: 99%